Inovasi Sistem Informasi Sekolah Menggunakan CodeIgniter 3 untuk Optimalisasi Layanan di Sekolah Dasar - Aripin, Ahmad Nurul; Mujiyono, Sri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Elementary schools as educational institutions require an information system that is fast, transparent, and easily accessible to the public. However, many schools still do not have a website-based information system, including SD Negeri X, which until now has relied on manual methods for delivering information. This condition creates limitations in disseminating information related to school profiles, teacher data, learning activities, and academic achievements. This study was conducted to address this need by developing a school information system based on a website using the CodeIgniter 3 framework and the Waterfall development method. The system was built with the PHP programming language and MySQL database, and tested using Black-Box Testing to ensure that all features functioned according to user requirements. The results showed that the developed application facilitates schools in providing information to the community, expands the school’s promotion reach, and improves the efficiency of data management, which can be accessed anytime via digital devices. Keywords: School Information System; Website; CodeIgniter 3; Waterfall; Black-Box Testing; Education Digitalization